A Retrospective Study of Nasopharyngeal Carcinoma: Clinical and Treatment Outcome - Madhu, Megha; Saldanha, Marina; Bhat, Vadish; Aroor, Rajeshwary (Journal of Health and Allied Sciences NU, 2024)
Background Nasopharyngeal carcinoma is an uncommon disease endemic to Southern China, Southeast Asia, North Africa, and the Arctic. It is uncommon in southern India, and hence its treatment outcome and prognosis are not widely studied in these areas. In this study, our primary objective was to document the clinical presentation of patients with nasopharyngeal carcinoma in southern India and to analyze the response to treatment and follow-up.Materials and Methods The study is an institutional-based retrospective study including 26 patients with histology-proven nasopharyngeal carcinoma from January 2011 to December 2017. All patients were treated with standard protocol of intensity modulated radiotherapy with concurrent chemotherapy. Data on patient demographics, clinical presentation, treatment, and follow-up were analyzed.Results The median age at presentation in our study was 53.5 years. The most common histopathology subtype was nonkeratinizing undifferentiated carcinoma (65%). Nodal metastasis was the most common clinical presentation seen in 88% of the patients. Post-treatment, distant metastasis to the iliac bone, lung, liver, and spleen was seen in two patients. Complete remission was achieved in 65%, whereas three patients developed recurrence after the completion of treatment. Five-year progression-free survival was 69%.Conclusion Nasopharyngeal carcinoma has a good response to concurrent chemoradiation. Long-term follow-up and planning surveillance strategies are essential post-treatment. Disease awareness to aid in early diagnosis and optimize management is imperative as observed from the delayed presentations in southern India.
Keywords: nasopharyngeal carcinoma; nonkeratinizing undifferentiated carcinoma; concurrent chemoradiation; metastasis; endemic locations